Journey to Union: Exploring Ibn Arabi’s Nomadic Philosophy and Imaginal Spaces in Sufism - Bouchoir, Tayeb; Acim, Rachid (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2023)
This paper sheds light on Ibn Arabi’s philosophy of journey, which takes place in an empty space where mystical characters, noble saints, Prophets and Messengers of God are given a chance to communicate and interact peacefully. Considering the hermeneutics’ approach to Sufi discourse and Gilles Deleuze’s concept of nomad thought, we aim to showcase that Ibn Arabi regards the Sufi wayfarers as “nomadic subjects” as long as they can journey to the inward and outward realms. The intersection of these two antagonistic realms— the realm of Seen (al-hiss) and Unseen (al-ghayb)— liberates the Sufi practitioners from spatio-temporal stagnation and transfers them to endless states and multiple becomings that later evolve into spiritual stations (maqāmāt) of stability and certainty. Contribution: This article highlights the breadth of Ibn Arabi’s nomadic style of thought in shaping the spiritual journey, arguing that the need to unite with God is expressed through a new style of spiritual movement that occurs in an imaginal space where the Sufi is enabled to communicate via his/her heart with other absentees, including noble saints, Messengers of God and Prophets